Effect of subchronic exposure to mainstream cigarette smoke on endothelium-dependent vasodilation in rat arteries - Lenasi, Helena (Zdravniški vestnik, 2005)
Abstract - Background. Cigarette smoking is reported to impair endothelium-dependent vasodilation. The aim of the present study was to assessthe effect of 30-day exposure to mainstream cigarette smoke on vascular reactivity of rat abdominal aorta, carotid, renal and mesenteric artery. Separately, the NO-mediated and the EDHF-mediated, endothelium-dependent vascular relaxations were determined. Methods. Two groups of Whistar Kyoto rats were exposed to mainstream cigarette smoke (2 hours/day, 5 days/week for 30 days) and to fresh conditioned air, respectively. Rats were sacrificed on the second day after the last exposition to cigarette smoke. Vascular reactivity studies were performed on isolated, endothelium-intact, phenylephrine preconstricted rat artery rings. Cumulative concentration-relaxation curves to acetylcholine (ACh) were obtained in the absence and presence of the endothelial NO synthase (eNOS) inhibitor N nitro L-arginine (L-NA) and the cyclo-oxygenase (COX) inhibitor diclofenac, respectively. After washing period of 1 hour, vessels were exposed either to the intracellular superoxide scavenger tiron, to the cytochrome P450 (CYP) inhibitor miconazole or the Na-K-ATPase inhibitor ouabain before being preconstricted with phenylephrine and determining the concentration-response curve to ACh. Results. ACh induced concentration-dependent relaxations. In none of the vessels investigated did we observe a significant difference in the relaxations obtained in arteries from control rats and rats exposed to cigarettee smoke. (Abstract truncated at 2000 characters)
Keywords: Acetilholin; Acetylcholine; Aorta; arterije; Carotid Arteries; Dušikov oksid; endotelij; Endotelij žilni; Endotelini; Endothelins; Endothelium, Vascular; kajenje; Karotidne arterije; Ledvična arterija; Mesenteric Arteries; Mezenterične arterije; Nitric Oxide; Noradrenalin; Norepinephrine; okvare; ožilje; podgane; Podgane seva WKY; Rats, Inbred Wky; Renal Artery; Tobacco Smoke Pollution; Tobačni dim, onesnaženje; Vasodilation; Vazodilatacija